Features of Control at a Hydro Power Plant - Norkhojayeva Nargiza Nasirovna (Genius Journals, 2023)
in this article, the main functions, control of modes and elements of modes of hydro power plants are considered, conclusions are given.
Keywords: hydroelectric power plant; energy; regime